2021
DOI: 10.1155/2021/3883204
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on the Role of Inflammatory Mechanisms in the Development of Postoperative Cognitive Dysfunction

Abstract: Postoperative cognitive dysfunction (POCD), as one of the common postoperative complications, mainly occurs after surgery and anesthesia, especially in the elderly. It refers to cognitive function changes such as decreased learning and memory ability and inability to concentrate. In severe cases, there could be personality changes and a decline in social behavior. At present, a great deal of research had been carried out on POCD, but its specific mechanism remains unclear. The release of peripheral inflammatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 156 publications
(153 reference statements)
0
27
0
Order By: Relevance
“…Briefly speaking, there are probably a couple of reasons for studying inflammation: on the one hand, inflammation can be regarded as a bridge connecting the cardiac surgery and neurocognitive disorders. Through upregulating cyclooxygenase 2 isozyme (COX-2) and matrix metalloproteinases (MMPs), peripheral pro-inflammatory cytokines can disrupt the integrity of the blood-brain barrier (BBB), allowing bone-marrow-derived monocytes (BMDM) to activate microglia cells and trigger neuroinflammation (Tan et al, 2021 ). Besides, Thackeray et al ( 2018 ) reported that biphasic peaks of neuroinflammation in early acute and late chronic stages of cardiac injury were similar to a biphasic microglial activation pattern with peaks at initial onset of mild cognitive impairment and late advanced Alzheimer's disease.…”
Section: Resultsmentioning
confidence: 99%
“…Briefly speaking, there are probably a couple of reasons for studying inflammation: on the one hand, inflammation can be regarded as a bridge connecting the cardiac surgery and neurocognitive disorders. Through upregulating cyclooxygenase 2 isozyme (COX-2) and matrix metalloproteinases (MMPs), peripheral pro-inflammatory cytokines can disrupt the integrity of the blood-brain barrier (BBB), allowing bone-marrow-derived monocytes (BMDM) to activate microglia cells and trigger neuroinflammation (Tan et al, 2021 ). Besides, Thackeray et al ( 2018 ) reported that biphasic peaks of neuroinflammation in early acute and late chronic stages of cardiac injury were similar to a biphasic microglial activation pattern with peaks at initial onset of mild cognitive impairment and late advanced Alzheimer's disease.…”
Section: Resultsmentioning
confidence: 99%
“…Presently, there are several hypotheses about the pathogenesis of POCD, which are related to inflammation of the central nervous system, nerve cell apoptosis, dysfunction of the cholinergic nervous system, and oxidative stress injury. However, inflammation of the nervous system still plays an important role in the development of POCD [ 16 , 32 , 33 ]. According to our previous study, microRNA-221-3p could target IRF2 of astrocytes to increase IFN-α expression and regulate nervous system inflammation [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the study, it is found that neuroinflammation can promote the release of peripheral inflammation-related factors (IL-1β, IL-6, TNF-α, IL-17, etc. ), destroy the protective effect of the blood-brain barrier on the center, induce central inflammation, and lead to neuronal apoptosis and synaptic loss [16]. In mice, surgery and anesthesia increased the expression of the high mobility group box-1 (HMGB1) in the cerebral cortex and hippocampus [17].…”
Section: Pocd and Inflammatory Reactions Of The Central Nervous Syste...mentioning
confidence: 99%